Investigation on Tattoo Ink (Hexadecachlorinate Copper Phthalocyanine) Removal: Novel Chemical and Biological Approach - Giancarlo Ranalli; Alessia Andreotti; Maria Perla Colombini; Cristina Corti; Debora Paris; Laura Rampazzi; Gabriella Saviano; Ramona Vecchio; Claudio Caprari (Molecules)
Tattoos have been a ubiquitous phenomenon throughout history. Now, the demand for tattoo removal for aesthetic or practical reasons is growing rapidly. This study outlines the results of field investigations into the chemical and biological removal of tattoo inks (Hexadecachlorinate copper phthalocyanine—C32Cl16CuN8—CAS no° 1328-53-6). FTIR, Py-GC/MS, and NMR analyses yielded intriguing profiles pertaining to the primary chemical constituents, along with others of an ambiguous nature. A bioremoval protocol was developed on a pork rind surface to simulate human tattooing. Two previously studied microbial strains were included in this analysis: (i) a bacterial culture of Pseudomonas stutzeri 5190 DSMZ viable cells and (ii) a fungal culture of Alternaria infectoria strain NIS4, the latter already isolated and identified. A combination of physical, chemical, and microbiological analyses, along with microscopic observations, was conducted. In our experimental conditions, inocula from environmental samples (soil and compost) were capable of inducing changes in even trace organic matter (glycerin and additives in pigments) used as a binder in emulsifiers in tattoo inks. Furthermore, the two microbial strains demonstrated promising potential for removing green tattoo ink. Finally, wastewater effluents containing green ink were recovered via electrochemical treatment, and the environmental impact in terms of the CO2 equivalent of our experiments was assessed. The results are promising and warrant further investigation into the innovative biological and chemical removal of tattoo inks from human skin and wastewater, respectively.